Subject-specific geometrical detail rather than cost function formulation affects hip loading calculation*. Issue 14 (25th October 2016) - Wesseling, Mariska; De Groote, Friedl; Bosmans, Lode; Bartels, Ward; Meyer, Christophe; Desloovere, Kaat; Jonkers, Ilse
Abstract: This study assessed the relative importance of introducing an increasing level of medical image-based subject-specific detail in bone and muscle geometry in the musculoskeletal model, on calculated hip contact forces during gait. These forces were compared to introducing minimization of hip contact forces in the optimization criterion. With an increasing level of subject-specific detail, specifically MRI-based geometry and wrapping surfaces representing the hip capsule, hip contact forces decreased and were more comparable to contact forces measured using instrumented prostheses (average difference of 0.69 BW at the first peak compared to 1.04 BW for the generic model). Inclusion of subject-specific wrapping surfaces in the model had a greater effect than altering the cost function definition.